If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(m + -13) + -5 = -9 Reorder the terms: -2(-13 + m) + -5 = -9 (-13 * -2 + m * -2) + -5 = -9 (26 + -2m) + -5 = -9 Reorder the terms: 26 + -5 + -2m = -9 Combine like terms: 26 + -5 = 21 21 + -2m = -9 Solving 21 + -2m = -9 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -2m = -9 + -21 Combine like terms: 21 + -21 = 0 0 + -2m = -9 + -21 -2m = -9 + -21 Combine like terms: -9 + -21 = -30 -2m = -30 Divide each side by '-2'. m = 15 Simplifying m = 15
| 5*8(2*9)/4 | | -(8x+12)=(3x-(-13)) | | 3q-15=9+5q | | (X/7)=-4 | | f(-20)=0.25x+260 | | 12w-10w-2=14 | | Y=(1/2)^2-1/2-42 | | 5*sin(x)=3-cos(2x) | | -16u+11u+10=-20 | | 1.8n=0.5n-11.44 | | 3x+6=-111-10 | | -6.6r=-4.7r+13.3 | | 3.1(f-14)+6.7=12.9 | | 5y+12=92 | | 9x+3=(-9x-10) | | -12.3b-12.95-9.94=-7.71-11.2b | | 4(5x-7)=10x+3 | | -2.6h+10.9=-4.4h-14.84 | | (3-x)=4 | | -14.87-4.5f=-3f+13.93 | | 3x+[4(x-1)]=45 | | -5.8f-13.89=-4.3f+12.96 | | y=4a+4a | | 14h+10=11h-8h-12 | | 2-13y=-13-14y | | 13h-12h+1=20 | | 12n+24=60 | | k^2+15k-25=0 | | 19j+18=18j | | 2n-n=7 | | -p-9=7p-1 | | 3/4x7= |